Penyelesaian Sengketa Internasional secara Damai - Irawan, Muhammad Aria Fachri; Sidqi, Muhammad Fahmi; Nufus, Neli Zakiyatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine how to resolve international disputes peacefully using descriptive analytical normative juridical methods that identify, analyze, clarify and construct phenomena based on observations as well as actual events and problems with existing reality, research This is a qualitative approach and data used. Peaceful resolution of international disputes, namely negotiation, is a general and efficient dispute resolution method, where the parties can monitor the process and reach a mutual agreement, fact finding is a dispute resolution method that focuses on clarifying the facts that are the source of the dispute, good services is a dispute resolution method in which a third party helps reconcile the disputing parties through negotiation. Mediation is a dispute resolution method that involves a neutral third party such as a state, international organization, or individual who plays an active role in the negotiation. Conciliation is a more formal dispute resolution method. rather than mediation, involving a third party or conciliation commission which can be permanent or ad hoc.